PENGARUH KOMPETENSI TERHADAP KINERJA PERAWAT BANGSAL RAWAT INAP DI RSUD dr. SOEHADI PRIJONEGORO SRAGEN - Berliana, Ovinda Cantika; Noor, Hesty Latifa; Trijono, Agus (Jurnal Keperawatan Duta Medika, 2024)
Introduction: Human resources are the most important determining factor in achieving the strategic goals of an organization, especially in the healthcare industry. Based on the results of a preliminary study, inpatient ward nurses have education ranging from third diploma to bachelor's degree to postgraduate degree, and inpatient indicators meet the ten standards set by the Indonesian Ministry of Health. The competence of nurses in terms of knowledge and skills in nursing is very important to know how good the performance of nurses is in achieving good health goals in accordance with the duties and authority, code of ethics and applicable standard operating procedures. Objectives: The purpose of this study was to determine the effect of competence on the performance of inpatient ward nurses at RSUD Dr. Soehadi Prijonegoro Sragen Methods: This study used a quantitative paradigm with a cross-sectional design to test the hypothesis. The study population consisted of all nurses (N = 158) in 11 inpatient wards. The study sample consisted of 121 nurses selected using proportional random sampling technique. The predictor variable was competence and the criterion variable was nursing performance. The analysis used univariate and bivariate analysis (simple linear regression analysis). Results: Based on univariate analysis, competence and performance are in the "good" category, with the percentage of competence of 95.87% and nurse performance of 92.56%. Based on bivariate analysis, the significance value is 0.000 <0.05 and t count is 8.796> t table 1.980. The results of the study indicate that competence has a positive influence on the performance of nursing staff. Conclusions: The conclusion is that competence has a positive effect on the performance of the inpatient ward hospital Dr. Soehadi Prijonegoro Sragen Regional Hospital.